Aetiology of cirrhosis, hepatic fibrosis, and hepatocellular carcinoma. Issue 6 (June 1977) - Blenkinsopp, W K; Haffenden, G P
Abstract : Histological study of 69 cases of cirrhosis, 9 of severe generalised hepatic fibrosis, and 19 of hepatocellular carcinoma showed an association with alcohol, hepatitis B surface antigen (HBsAg) or a1-antitrypsin bodies in, respectively, 41 (cirrhosis), 5 (fibrosis), and 9 (carcinoma). Eight of the cirrhotic cases and two of the carcinoma cases had double associations, HBsAg being present in all. Torcein and aldehyde fuchsin staining gave both false positive and false negative results when compared with immunofluorescence and immunoperoxidase methods for HBsAg. Large amounts of copper were found in four cirrhotic livers, and moderate amounts in 13: the diagnostic value of copper staining is questioned.